FAKTOR- FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PREEKLAMPSI BERAT (PEB) - Novrianti, Silpia; Rachmawati, Rachmawati; Yuniarti, Yuniarti (Politeknik Kesehatan Kemenkes Bengkulu, 2018)
Severe preeclampsia (PEB) is still one of the causes of maternal morbidity and mortality if not adequately treated. There are many things that affect the occurrence of PEB, some of which are maternal age, parity, gestational age and education. The high incidence of PEB in the 2016. Yunus Bengkulu District Hospital Obstetric Room in 2016. The purpose of this study was to determine the factors that influence the incidence of PEB in Yunus Bengkulu Public Hospital in 2016. The design of this study was using case control, with a maternal population 1070 people in 2016 with a sample of 162 people. The analysis was carried out univariately and bivariately using Chi-Square test while multivariate analysis used Logistic Regression test. The results showed that there was a relationship between age, parity, gestational age and education with the incidence of PEB. The results of multivariate analysis showed that education had the most influential relationship to the incidence of severe preeclampsia.